Some perceptions about the feminine and the masculine: Young people speak - Ochoa Rivero, Silvia (1993)
The article that we present below collects and suggests clues for reflection about what masculine and feminine mean for adolescents and young people between 14 and 19 years of age in the southern Andean urban context. For this work we take as base material, on the one hand, the observation records of the expressions of some young people in sexuality workshops and, on the other, the surveys elaborated and developed between 1991 and 1992 in the so-called "big towns" of Cusco. (Yanaoca, Pampamarca, Tungasuca), in the context of participatory research "South Andean youth share their problems and perspectives". In this material we inquire about the perception of young people regarding the sexual roles that are assigned to each gender and how they are submerged by them.